METODE PENDIDIKAN KARAKTER PERSPEKTIF KOMUNIKASI MELAYU: TELAAH TERHADAP NASKAH TĀJ AS-SALĀṬĪN KARYA BUKHARI AL-JAUHARI - Maryamah; Alimron; Agus Srimudin (Universitas Sumatera Selatan, 2021)
Communication is one of the effort to instill character in students in the world of education. The method of delivery through the Malay Communication Perspective is one of the effective efforts in communicating to the community, especially students. One of these methods is contained in the Taj as-Salatin manuscript by Bukhari Al-Jauhari, which was studied by the research team in this journal. In the book of Taj as-Salatin discusses ethics, politics, and government which are often found in character education. Character education can be divided into four categories, namely character education in relation to Allah SWT, oneself, fellow human beings, and the environment.